Operation Pollinator: Positive Action for Pollinators and Improved Biodiversity on Farm. (1st June 2020) - Sutton, Peter
Operation Pollinator is an industry led initiative. This biodiversity enhancement programme has enabled better engagement and training of farmers in the delivery of high quality wildlife habitats as part of their national agri-environment schemes (AES). This overview presents findings from farm-scale studies that have shown the type and scale of effects required to deliver such benefits on farm and across the landscape. Significant efforts have already been made to promote biodiversity on farmland, but these results show that to improve the agricultural landscape really, we need to implement more of the best options so as to achieve the scale required to underpin the delivery of ecosystem services. The UK is still transitioning from the old Agricultural Policy Scheme (CAP) scheme, and so it will still be possible to use this type of off-crop mitigation to protect wildlife and ecosystem services in future AES, and this strategy has been described as using "public money for public goods" or "payment for ecosystem services. The EU has proposed that farmers manage 5–7% of the landscape in this way and field margins are a critical mechanism for such farmland biodiversity programmes. The results presented are from a selection of farm scale studies (i.e. with plots of 40 ha – 100 ha) that were large enough to provide indications of the scale of implementation required as targeted AES measures to benefit both farmland birds and pollinators. This review is based on an earlier paper that was presented at a conference on "Sustainable Intensification" organised by the Association of Applied Biologists in 2016. Ref: Aspects of Applied Biology 136, 2017 Sustainable Intensification p120–129 Operation Pollinator: Positive action for pollinators and improved biodiversity in arable landscapes, Peter Sutton, Geoff Coates, Belinda Bailey, Marek Nowakowski, Mike Edwards, Robin Blake, Ben Woodcock, Claire Carvell & Richard Pywell.